Manufacturing Servitization in the Asia-Pacific - Wang, Jing; Kosaka, Michitaka; Xing, Ke (Springer Nature Singapore : Imprint: Springer, 2016)
This book systematically describes the development of manufacturing servitization in the Asia-Pacific region. It offers a practical and theoretical reference guide to the manufacturing companies in the Asia-Pacific region, which is now a major global manufacturing center. Servitization is a fairly recent trend in the manufacturing industry: some American and European manufacturing companies have successfully transformed to service oriented manufacturing companies over the past three decades, while Asian-Pacific region companies have only more recently begun to recognize the importance of servitization. But some Asia-Pacific region companies have been exploring approaches in the same direction of servitization without being aware of the concept. One unique aspect of this book is the fact that it takes into consideration the social and cultural influences of this region. It introduces companies within and beyond the region, as well as the academic world, to the current state of development of the Asia-pacific manufacturing industry and its servitization trend. This is the first book that focuses on this topic, one which is of great theoretical and practical importance.